The Role and Function of Mucins and Its Relationship to Inflammatory Bowel Disease - Kang, Youra; Park, Hyeonjeong; Choe, Byung-Ho; Kang, Ben (Frontiers in Medicine, 2022)
The mucus layer is an essential component of the human intestinal barrier since it protects the barrier, regulates intestinal microbiome homeostasis, and prevents disease. Mucin (MUC)-2 is a secreted protein produced by epithelial goblet cells as a major component of mucus. In this review, we summarize MUC2 mucin features and its role in intestinal disease. Furthermore, we examined whether the role of MUC2 mucin differed between children and adults, and ulcerative colitis (UC) and Crohn’s disease (CD).